CAMPUR KODE PADA BERITA UTAMA BALI ORTI BALI POST - Indah Prabandari, Ni Putu (Humanis, 2015)
The study on mixing code headlines Bali Orti Bali Post aimed to describe the forms of code mixing, code mixing characteristics, as well as the factors that cause code mixing. This study took a sample of the data for the first of five years of the publication of Bali Orti in the year 2006-2011. The theory used is the sociolinguistic theory proposed by Jendra and Nababan, which refers to the concepts associated with code mixing. Methods and techniques used in this study were divided into three stages namely, 1) the stage of providing data using methods refer assisted with technical notes, 2) data analysis stage using methods agih aided by using techniques for direct elements, 3) stage presentation of the results of data analysis used informal methods aided by deductive and inductive techniques. The results obtained in this study are code mixing forms of governance seen level linguistic device that is tangible words and phrases. In the words found in the base word and derived word (having affixation, reduplication, and compound words). Various mixed origin code based on three kinds of absorption is inner code mixing, outer code mixing which is derived from English and Latin, and hybrid code mixing which is derived from the mixing Indonesian and English. The characteristics of code mixing is 1) code mixing event is not required by the situation and the context of the discussion, but rather depends on the speakers (language functions), 2) the code mixing occurs because of your relaxation and habit, 3) code mixing occurs at the level of the lowest form of words and highest form of clauses, 4) language elements that insert into the Balinese language no longer supports language function independently but are united by language inserted. Factors causing mixed on the news headlines Bali Orti Bali Post motivated by two factors, namely factors language speakers and the media factors.
Keywords: sociolinguistics, code mixing, headlines, and Bali Orti